NIHIL NOVI – CONTENT AND LANGUAGE INTEGRATED LEARNING IN ENGLAND AND THE ENGLISH BY WŁADYSŁAW KOSPOTH-PAWŁOWSKI - Kiński, Czesław; Łagun, Jacek (Neofilolog, 2018)
The article presents the language coursebook entitled England and the English by Władysław Kospoth-Pawłowski, published in Poland in 1930. Written a long time before the emergence and development of Content and Language Integrated Learning, the book may be perceived as original, innovative and ahead of its times in terms of the methodology applied. Several references to subsequent educational theories are made to emphasize the originality and the unique, modern nature of the book.